(untitled) (Marketing Journal, 2025)
The article proposes strategic management and institutional approaches aimed at ensuring the sustainable development of the food products market in Uzbekistan. It highlights the role of regional disparities, resource utilization efficiency, public -private sector cooperation, and institutional mechanisms. As a result of the study, strategic approaches to achieving stability in the food market are presented. Additionally, a comparative analysis of the food security situation in the Republic of Uzbekistan and several other countries is conducted based on the Global Hunger Index (GHI).